The association Veronico-Mimuletum guttati Niemann 1965 in Pomerania - Sobisz, Zbigniew; Osadowski, Zbigniew; Truchan, Mariola (Biodiversity: Research and Conservation, 2015)
Veronico-Mimuletum guttati, a poorly known association of species-rich helophyte beds communities was characterizedbased on 21 phytosociological relevés. Its new 14 localities in Pomerania and floristic differentiation in Central Europe are presented. New subassociations of the Veronico-Mimuletum guttati cardaminetosum amarae have been distinguished on the basis of differing floristic composition. It is further differentiated into two syntaxa: spring variant noted in spring areas and typical variant noted in banks of rivers, ditches and water-logged meadows.